Perbandingan Data Penjulan Multivitamin Apotek “X” Kecamatan Tarik Kabupaten Sidoarjo Sebelum Pandemi (Periode Januari 2020) Dan Disaat Pandemi (Periode Januari 2021) - rifdah atikah; Supomo (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstract The role of the pharmacy is very important in providing drug availability which is very high. Methods: This study used observation and in-depth interviews. In determining the number of samples using total sampling technique. The instruments used were data collection sheets (Observation) and interviews with the pharmacists of pharmacy X, Tarik district. Results: The results of this study regarding a comparison of multivitamin sales data at the “X” District of Tarik pharmacy before the pandemic (January 2020) and during the pandemic (January 2021) obtained results based on observational data stating that multivitamin sales in the pre-pandemic period (January 2020) with a total of 252 with a percentage of 32%, and sales of multivitamins during a pandemic (January 2021) with a total of 529 with a percentage of 68%. That means that sales of multivitamins during the pandemic (January 2021) experienced a significant increase, namely at 36% compared to before the pandemic (January 2020). It was proven that during the pandemic (January 2021) the